"Onion skin" sign in an ovarian mucinous cyst. Issue 1 (16th January 2012) - Perlman, Sharon; Hazan, Yenon; Hagay, Zion; Appelman, Zvi; Caspi, Benjamin
Abstract The sonographic "onion skin" sign was initially described as concentric echogenic layers in mucinous tumors unrelated to the female reproductive system. Typically, the sonographic appearance of ovarian mucinous cystadenoma includes numerous septa and fine, gravity‐dependent echoes. We present a case of the "onion skin" sign in a mucinous ovarian tumor. © 2012 Wiley Periodicals, Inc. J Clin Ultrasound 2013